2021
DOI: 10.1101/2021.09.20.461121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cellular Reference Resource for the Mouse Urinary Bladder

Abstract: The urinary bladder functions as a reservoir to store and extrude liquid bodily waste. Significant debate exists as to this tissue's cellular composition and genes associated with their functions. We use a repertoire of cell profiling tools to comprehensively define and spatial resolve cell types. We characterize spatially validated, basal-to-luminal gene expression dynamics within the urothelium, the cellular source of most bladder cancers. We define three distinct populations of fibroblasts that spatially or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Convergence of strands of technologies, including more powerful computing infrastructure, decreasing cost of sequencing, and the generation of more quantitative data, have mainstreamed and revolutionized spatial transcriptomics and opened up new possibilities. However, the legacy of the prequel era still lives on in the usage of prequel resources, such as referencing the Allen Brain Atlas (ABA) 32 and the Allen Mouse Common Coordinate Framework 33 , and in institutions such as the Allen Brain Institute and the Jackson Laboratory, which are contributing to the current era of research 34,35 .…”
Section: Prequel Eramentioning
confidence: 99%
“…Convergence of strands of technologies, including more powerful computing infrastructure, decreasing cost of sequencing, and the generation of more quantitative data, have mainstreamed and revolutionized spatial transcriptomics and opened up new possibilities. However, the legacy of the prequel era still lives on in the usage of prequel resources, such as referencing the Allen Brain Atlas (ABA) 32 and the Allen Mouse Common Coordinate Framework 33 , and in institutions such as the Allen Brain Institute and the Jackson Laboratory, which are contributing to the current era of research 34,35 .…”
Section: Prequel Eramentioning
confidence: 99%
“…Changes in cell composition may contribute to dysfunction in the aging bladder. Single cell transcriptomics of the B6 mouse bladder found that aged animals exhibit nearly an 11% increase in the proportion of fibroblasts in comparison to both young or mature animals (Baker et al, 2021 ). Further, the same study found an increase in the ratio of mesenchymal to urothelial cells (Baker et al, 2021 ), a particularly important observation given that the epithelial‐to‐mesenchymal transition has been associated with tumor progression and a driver of poor prognosis in plasmacytoid urothelial carcinoma (Nomura et al, 2020 ).…”
Section: Changes With Aging Along the Brain–bladder ...mentioning
confidence: 99%
“…Single cell transcriptomics of the B6 mouse bladder found that aged animals exhibit nearly an 11% increase in the proportion of fibroblasts in comparison to both young or mature animals (Baker et al, 2021 ). Further, the same study found an increase in the ratio of mesenchymal to urothelial cells (Baker et al, 2021 ), a particularly important observation given that the epithelial‐to‐mesenchymal transition has been associated with tumor progression and a driver of poor prognosis in plasmacytoid urothelial carcinoma (Nomura et al, 2020 ). Another single cell bladder atlas reported that aging was associated with decreased mesenchymal and increased urothelial cell proportions (Tabula Muris, 2020 ), although these samples were denuded (detrusor muscle removed) which may explain this discrepancy.…”
Section: Changes With Aging Along the Brain–bladder ...mentioning
confidence: 99%